Real-world use of tafasitamab preceding CD19-directed chimeric antigen receptor T-cell therapy for relapsed or refractory diffuse large B-cell lymphoma - Narendranath Epperla; Loretta J. Nastoupil; Bruce Feinberg; John Galvin; Prathamesh Pathak; Theresa Amoloja; Danielle Gentile; Kim Saverno (Biomarker Research)
Abstract Potential CD19 antigen loss following CD19-directed therapy has raised concerns over sequential use of these therapies. Tafasitamab, a CD19-targeting immunotherapy, combined with lenalidomide, is approved for relapsed or refractory diffuse large B-cell lymphoma (R/R DLBCL) treatment in adults ineligible for autologous stem cell transplantation. This retrospective analysis examined characteristics and outcomes of adults with R/R DLBCL who received tafasitamab preceding CD19-directed chimeric antigen receptor T-cell (CAR-T) therapy in a real-world setting. Nine patients received tafasitamab and lenalidomide immediately preceding CAR-T. Median (first quartile [Q1]–third quartile [Q3]) follow-up time since tafasitamab initiation was 26.1 (18.0–28.0) and after CAR-T was 9.3 (1.9–16.7) months. Of the 9 patients, 4 had complete response, 4 had partial response, and 1 had stable disease following tafasitamab; all discontinued tafasitamab due to disease progression. Median (Q1–Q3) tafasitamab therapy duration was 11.0 (8.1–14.1) months. Three patients had CD19 testing following tafasitamab discontinuation, and all tests were positive. Median (Q1–Q3) time from tafasitamab discontinuation to CD19 testing was 7 (6–9) days. Among the 9 patients, median (Q1–Q3) time from tafasitamab discontinuation to CAR-T administration was 3.2 (2.3–3.6) months. Four patients had complete response, 3 had partial response, and 1 had progressive disease as best response to CAR-T; 1 patient had data unavailable. This small real-world analysis demonstrated disease response to CAR-T therapy and detectable CD19 expression following tafasitamab treatment, adding to literature investigating treatment outcomes associated with sequential use of anti-CD19 therapies in patients with R/R DLBCL.